Preparation of wells using an electrohydraulic drill and modeling of heat transfer processes in heat transfer elements of a heat pump - Akhmadiyev, B.; Zhetimekova, G.; Duisenbayeva, M.; Sharzadin, A.; Nussupbekov, B. (Eastern- European Journal of Enterprise Technologies, 2023)
The article discusses the use of innovative electrohydraulic technology in the preparation of vertical ground heat exchangers to create heat supply using heat pumps. The discharge energy in the operating range varied E = 900÷2600 J. The most economical mode of operation of the electrohydraulic installation is carried out with the following parameters: discharge voltage 30÷51 kV, capacitor bank capacity 2 μF and interelectrode distance 8÷15 mm. It is determined that the optimal energy of destruction of natural materials depends on their thickness. Based on the research, the limits of the electrophysical parameters of the approach were established, at which the concentrated destruction of hard rocks – the main stones – begins. The effective amount of energy for the destruction of stones with a thickness of 53 mm is 900 J. For stones with a thickness of 78 mm, there should be 2600 J. If to increase the energy of the discharges to 1837 J, the process of complete destruction of the stones is underway. Using an electro hydraulic drill, we have prepared vertical wells up to 25 m deep. In the future, we have installed special temperature sensors along the length of the pipes, inside the well. Using a software product (Temp Keeper), data from temperature sensors are received in real time. This program allows to visually monitor temperature changes occurring at a local point. Temperature and time dependences are also obtained at coolant velocities of 0.2÷0.4 m/s. A significant decrease in the temperature in the well and at the outlet was observed at a coolant velocity of 0.35 m/s for one hour. The study conducted on the basis of the data obtained enables to achieve higher optimal drilling performance compared to conventional installations
Keywords: electrohydraulic drilling; borehole; heat exchanger; discharge voltage; fracture energy; modeling